An Analysis Student’s Ability in Writing Descriptive Text of Second Semester of English Educational Program at STKIP Nurul Huda Oku Timur - Zulaikah Zulaikah; Eka Agustina; M. Muklas (IAI Darussalam, 2018)
This study was descriptive research. The objective this study was “to find out whether descriptive methode can analyse writing ability in second semester of English Educational Program at STKIP Nurul Huda OKU Timur”. The students’ writing ability in descriptive text was analyzed based on score clasification. In this case, the highest score of 32 students in this class, get 75 which it considered the as in good level. While the lowest results get score 52 which it considered the as in average level. Then, the other students’ get 54 until 74 mean score in terms of sub indicator in writing text they get was in which it also considered as in average and good level. Thus, generally, the students’ mean score of writing ability particularly in writing descriptive text was 60 and it was considered as the average level of ability. Thus, from the data presentation, it can be concluded that the writing descriptive text skill of the second semester of English educational program in STKIP Nurul Huda was in average level